Prevalence and Risk Factors of Needlesticks and Sharp Injuries Among Healthcare Workers of Hospital in Bule Hora, West Guji Zone, Ethiopia - Alqeer Aliyo; Tibeso Gemechu (SAGE Publishing, 2024)
Background: Healthcare workers face a significant risk of sharp and needle-stick injuries, which can increase the likelihood of spreading illnesses like hepatitis B, hepatitis C, and HIV. Currently, there is no available information on the prevalence or contributing factors of needle sticks and sharp injuries (NSSI) in hospitals in southern Ethiopia. Objective: This study aimed to assess the needle sticks and sharp injuries among health care workers at the BHUTH, Southern Ethiopia. Methods: The study was a cross-sectional study conducted at an institution in October 2023, with 164 randomly selected participants. A self-administered questionnaire was used to gather information on sociodemographic factors and exposure status. The data was entered and analyzed using Epi-Data and SPSS. The risk factors were identified by binary and multivariate logistic regression analyses. A P -value less than .05 was considered statistical significance. Result: The overall prevalence of at least one Needle sticks and sharp injuries in the last 12 months was 46.4% (95% CI of 39.3% to 53.6%). The majority of injuries 45.8% were due to the syringe needle. Factors such as needle recap (AOR = 3.73, 95% CI: 1.07-12.19), Recapping with two hands (AOR = 2.78, 95% CI: 1.36-10.02), working 40 hours per week (AOR = 2.18, 95% CI: 0.98-6.86), and lack of training in occupational safety practices (AOR = 4.01, 95% CI: 2.60-9.91), were factors significantly associated with the prevalence of needle stick and sharp injuries. Conclusions: This study found that nearly half of the respondents experienced a sharp needle poke and injury at least once in the previous year; however, the volume of NSSI remains high in the study area. Healthcare workers should receive on-the-job training, and hospital executives should set aside time for discussions on how to solve the problem.